HIV-positive migrants' encounters with the Swedish health care system. Issue 1 (1st December 2016) - Mehdiyar, Manijeh; Andersson, Rune; Hjelm, Katarina; Povlsen, Lene
Abstract : Background: There is limited knowledge about human immunodeficiency virus (HIV)-positive migrants and their experiences in the Swedish health care system. It is necessary to increase our knowledge in this field to improve the quality of care and social support for this vulnerable group of patients. Objective: The aim of this study was to describe the experiences of HIV-positive migrants and their encounters with the health care system in Sweden. Design: This is a Grounded Theory study based on qualitative interviews with 14 HIV-positive migrants living in Sweden, aged 29–55 years. Results: 'A hybrid of access and adversity' was identified as the core category of the study. Three additional categories were 'appreciation of free access to treatment', 'the impact of the Swedish Disease Act on everyday life', and 'encountering discrimination in the general health care system'. The main finding indicated that participants experienced frustration and discrimination because they were required to provide sexual partners with information about their HIV status, which is compulsory under the Swedish Disease Act. The study also showed that the bias or fear regarding HIV infection among general health care professionals outside of the infectious diseases clinics limited the access to the general health care system for HIV-positive migrants. Conclusions: The HIV-positive migrants appreciated the free access to antiviral therapy, but wished to have more time for patient–physician communications. The participants of this study felt discrimination in health care settings outside of the infectious diseases clinics. There is a need to reduce the discrimination in general health care services and to optimize the social support system and social network of this vulnerable group.